New Trends in Nanoarchitectured SERS Substrates: Nanospaces, 2D Materials, and Organic Heterostructures; Small; Vol. 18, iss. 25 - Guselnikova O. A. Olga Andreevna; Lim Hyunsoo; Kim Hyun-Jong; Kim Sung Hyun; Gorbunova A. Alina; Eguchi Miharu; Postnikov P. S. Pavel Sergeevich; Nakanishi Takuya; Asahi Toru; Na Jongbeom; Yamauchi Yusuke (2022, 2022)
Title screen